Characteristics of Soaked and Dried Water Yam Flour as Material for Producing Edible Paper - Indrastuti, Erning; harijono, Harijono; Susilo, Bambang (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
This research aimed to study the physicochemical characteristics of water yam flour are due to soaking and drying treatments, as material for edible paper, as a substitute for rice flour in the producing of rice paper (fresh spring roll wrapper). This study used Randomized Block Design with two factors: soaking time of 0, 24, and 48 hours; and drying temperature at 40, 50, and 60 °C. The result showed increasing soaking decreased mucilages, meanwhile increasing soaking time increased swelling power. Moisture content did not differ significantly (p>0.05). Soaking 24 hours produced the highest final viscosity at all drying temperature. Soaking 24-hour and drying temperature 50 °C treatment could be suggested for producing yam flour and was recommended as raw material for edible paper processing.Keywords: water yam flour, viscocity, swelling power, physichochemical properties, edible paper